2016
DOI: 10.1371/journal.pone.0167496
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Brucellosis and Genetic Diversity of Brucella abortus in Kazakhstan

Abstract: Brucellosis is a major zoonotic infection in Kazakhstan. However, there is limited data on its incidence in humans and animals, and the genetic diversity of prevalent strains is virtually unstudied. Additionally, there is no detailed overview of Kazakhstan brucellosis control and eradication programs. Here, we analyzed brucellosis epidemiological data, and assessed the effectiveness of eradication strategies employed over the past 70 years to counteract this infection. We also conducted multiple loci variable-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…Due to thehigh mutation rate in tandem DNA repeats loci, the MLVAplatform provides the ability to distinguish eld and vaccine strains [22], associate isolates with geographic origins, and discriminate most Brucella species with a high homogeneity discriminatory power [23]. In China, MLVA genotyping provides a basis for reliable disease monitoring when combined with strain phylogeny and regional and time distributions, thus potentially providing valuable insight when examining an epidemiological linkage or trace-back investigation during a brucellosis outbreak [13,24,25].Furthermore, previous studies have shown thatMLVA can be used as an epidemiological tool for strain resolution and to distinguish relapses from reinfections in brucellosis patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Due to thehigh mutation rate in tandem DNA repeats loci, the MLVAplatform provides the ability to distinguish eld and vaccine strains [22], associate isolates with geographic origins, and discriminate most Brucella species with a high homogeneity discriminatory power [23]. In China, MLVA genotyping provides a basis for reliable disease monitoring when combined with strain phylogeny and regional and time distributions, thus potentially providing valuable insight when examining an epidemiological linkage or trace-back investigation during a brucellosis outbreak [13,24,25].Furthermore, previous studies have shown thatMLVA can be used as an epidemiological tool for strain resolution and to distinguish relapses from reinfections in brucellosis patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high mutation rate in tandem DNA repeats loci, the MLVA-16 scheme provides the ability to distinguish eld strains [21] and associate isolates with their geographic origins [22]. In China, MLVA genotyping provides valuable insight when examining an epidemiological linkage or trace-back investigation during a brucellosis outbreak [10,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The disease causes not only great economic losses in animal husbandry, but also poses a serious threat to public health (2,15). A complicated epizootic and epidemiological situation for brucellosis persists in the Republic of Kazakhstan where the disease remains endemic (21,33). The efficacy of brucellosis control and eradication programs primarily depends on the timely detection of infected animals by serological tests.…”
Section: Praca Oryginalnamentioning
confidence: 99%